ESG (ENVIRONMENTAL, SOCIAL, GOVERNANCE) INDICATORS AND FINANCIAL ANALYSIS INTEGRATION: https://doi.org/10.5281/zenodo.15472398 - Musaeva, Nasiba (Journal of Contemporary World Studies, 2025)
This article extensively explores how ESG (environmental, social, and Corporate Governance) Indicators influence financial analysis. Today, with the global economy moving towards sustainability, ESG factors have become an important factor in assessing the company’s long-term sustainability and financial status. The study is based on the example of leading companies in Europe, statistically and practically analyzing the relationship between ESG performance and financial performance. The results show that companies that follow ESG principles manage better risks, build reliable relationships with stakeholders, and strengthen brand reputation. This, in turn, increases their attractiveness to investors and ensures their financial stability. The article brings important conclusions about how ESG indicators strengthen business strategy, openness, stability and responsibility.